Protective Behavioral Strategies Underutilization Mediates Effect of a Brief Motivational Intervention among Socially Anxious Undergraduate Drinkers - Terlecki, Meredith A. (Psychol Addict Behav, 2021)
Social anxiety (SA) is implicated in problematic undergraduate drinking. Brief motivational interventions (BMIs) reduce problematic undergraduate drinking. However, not all students benefit. Identification of vulnerable subgroups is an important next step. The current study examined the role of SA and protective behavioral strategies (PBS) on BMI outcomes. We reanalyzed a subset of data (53.3%; N = 120; 62.5% male) from a randomized trial in which heavy drinking undergraduates were randomized to a BMI or control. SA, past-month typical drinks, peak drinks, weekly quantity, alcohol problems, and PBS were assessed at baseline and 6-weeks. Main effects and interaction among the intervention condition (BMI vs. control) and SA group (low vs. high) were tested on alcohol outcomes and PBS. High SA undergraduates reported greater baseline drinking, more alcohol problems, and lower PBS. Post-BMI, high SA drinkers continued to report greater peak drinks, typical drinks, alcohol problems, and lower PBS use, controlling for baseline use. Among the BMI condition, parallel multiple mediation analyses revealed the PBS subscale Manner of Drinking uniquely mediated the relationship between SA and heavier post-BMI drinking. The PBS Manner of Drinking and Serious Harm Reduction subscales jointly mediated the relationship between SA and greater post-BMI alcohol problems. BMIs may need to be refined to improve outcomes for socially anxious drinkers. Increasing PBS utilization post-BMI may help improve BMI efficacy in this vulnerable group. Clinical implications are discussed.